2015
DOI: 10.1111/jav.00738
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐scale habitat use during the non‐breeding season suggests that winter habitat does not limit breeding populations of a declining long‐distance Palearctic migrant

Abstract: For migrant birds, which habitats are suitable during the non‐breeding season influences habitat availability, population resilience to habitat loss, and ultimately survival. Consequently, habitat preferences during winter and whether habitat segregation according to age and sex occurs directly influences migration ecology, survival and breeding success. We tested the fine‐scale habitat preferences of a declining Palearctic migrant, the whinchat Saxicola rubetra, on its wintering grounds in west Africa. We exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 77 publications
1
37
0
Order By: Relevance
“…This may not be the case in the Old World, however, where suitable wintering habitat may be more abundant (Newton ) and differences in quality between habitats not so well defined (Cresswell ). Indeed, there is no evidence of sex‐ or age‐based habitat occupancy for wintering Whinchats over the study area based on fine‐scale habitat characteristics (Blackburn & Cresswell ,b), although it is possible these habitat characteristics do not necessarily reflect prey abundance. A lack of segregation would be expected in an area with low competition (Whinchats are not at carrying capacity in this area; Hulme & Cresswell ) and where energy costs are low (Whinchats spend only 11% of the day foraging; Barshep et al .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This may not be the case in the Old World, however, where suitable wintering habitat may be more abundant (Newton ) and differences in quality between habitats not so well defined (Cresswell ). Indeed, there is no evidence of sex‐ or age‐based habitat occupancy for wintering Whinchats over the study area based on fine‐scale habitat characteristics (Blackburn & Cresswell ,b), although it is possible these habitat characteristics do not necessarily reflect prey abundance. A lack of segregation would be expected in an area with low competition (Whinchats are not at carrying capacity in this area; Hulme & Cresswell ) and where energy costs are low (Whinchats spend only 11% of the day foraging; Barshep et al .…”
Section: Discussionmentioning
confidence: 98%
“…Individuals hold small, discrete territories during the winter (Barshep et al . , Blackburn & Cresswell ), and their preference for open habitat and tendency to perch on low shrubs make them highly detectable (Hulme & Cresswell ).…”
mentioning
confidence: 99%
“…It has been suggested that, unlike open‐country migrant species (Cresswell et al . , Hulme & Cresswell , Blackburn & Cresswell , 2016), those species that are more dependent on shrubby and wooded habitats may suffer the consequences of the loss of native vegetation (Cresswell et al . , Mallord et al .…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly true for Afro‐Palaearctic migrants (Vickery et al . ), although this is improving (Blackburn & Cresswell , , Mallord et al . , Willemoes et al .…”
mentioning
confidence: 99%
See 1 more Smart Citation